MORPHOLOGICAL VARIATION OF MALAYOPYTHON RETICULATUS (SCHNEIDER, 1801) FROM SEVERAL POPULATION IN INDONESIA - Septiadi, Luhur; Fathoni, M; Hanifa, Berry Fakhry; Hamidy, Amir (Journal of Tropical Life Science, 2019)
Reticulated python (Malayopython reticulatus) is a widely distributed snake covering throughout Southeast Asia and almost all of Indonesia archipelago and divided into several subspecies based on morphological variation and its locality. Morphological variation data of M. reticulatus from Indonesia population has never been done thoroughly. This study aims to determine the morphological variations based on 21 meristic and 3 morphometric characters from several populations in Indonesia. The data was collected from the Museum Zoologicum Bogoriense (MZB) Cibinong, Indonesia and other additional collections that are carried out from June to July 2018 and then analyzed by Principal Component Analysis (PCA) to determine the population grouping. The result showed a high variation on the scale range of anterior prefrontal, posterior prefrontal, frontal, parietal, preocular, postocular, loreal, temporal, upper labial, lower labial, and dorsal scales. Ventral and subcaudal scales in male and female specimens show high variation in the total scale count, the ratio comparison of tl: SVL measurement, indicated the sexual dimorphism. Prefrontal (anterior-posterior) and frontal scales show high variation and difficult to distinguish between each locality at the subspecies level and suggest it to be intra-specific variation. There is no significant grouping were found between populations from data on morphological variations.